Gastroprotective Effects of the Aqueous Extract from Taraxacum officinale in Rats Using Ultrasound, Histology, and Biochemical Analysis - Zanatta, Maria Eduarda D. C.; Miorando, Daniela; Stefller, Amanda M.; Roos, Nátali; Ernetti, Jackeline; Predebon, Ana Júlia; Lindemann, Heloísa; Mânica, Aline; Oliveira, Beatriz M. M.; Serpa, Patrícia Z.; Bohnen, Lilian; Simomura, Viviane; et al. (Hindawi, 2021)
Taraxacum officinale F.H. Wigg. belonging to the family Asteraceae is an edible medicinal plant distributed worldwide. This study aimed to determine the gastroprotective effects of aqueous extract of T. officinale (AETo) in rats using ultrasound, histological, and biochemical analyses. In this study, gastric ulceration was induced by ethanol or piroxicam. Rats were then treated with AETo (3, 30, or 300 mg/kg). The area and histological appearance of gastric ulcers were quantified, and histochemical analysis was performed. The activity of AETo on inflammatory and oxidative stress markers was assessed in the ulcerated tissue. In addition, we investigated the thickness of the gastric wall using the ultrasound technique. Moreover, chemical analyses of AETo were performed. In rats with ethanol- or piroxicam-induced ulcers, AETo reduced the ulceration area, elevated mucin level, and the gastroprotective effect was confirmed by histological analysis. The gastroprotective effect was accompanied by increased activities of SOD, CAT, and GST, as well as an increase in GSH level and reduction in MPO activity. Furthermore, AETo reduced the thickness of the gastric wall in rats. Phytochemical analysis of AETo indicated phenolic acids and flavonoids as the main active compounds. In conclusion, the gastroprotective effect of AETo involves reduction in oxidative stress and inflammatory injury and increase in mucin content. This study advances in the elucidation of mechanisms of gastric protection of T. officinale, contributes to the prospection of new molecules gastroprotective, and proposes the ultrasonographic analyses as a new gastroprotective assessment tool in preclinical studies.